Kesan Ion Fosfat ke atas Jerapan Sulfat oleh beberapa Tanah Malaysia. - Taib, Samsiah; Abdul Rahman, Zaharah (1981)
The experiment on the effect of phosphate ion on sulfate adsorption in soils showed that phosphate ion is effective in exchanging with the adsorbed sulfate ions on the soil colloids. The quantity of sulfate ions adsorbed tended to decline with increasing amounts of P added. Sulfate desorption occurred when P concentration reached 200 g P g-1 soil for Bungor and Melaka series and 400 1kg P g-l soil for Padang Besar and Munchong series. This shows that these ions had different affinities for adsorption by the soils, and both ions seemed to go for the same adsorption sites